Remnant Cholesterol and Common Carotid Artery Intima-Media Thickness in Patients With Ischemic Stroke. (9th April 2021) - Qian, Sifan; You, Shoujiang; Sun, Yaming; Wu, Qiuyi; Wang, Xianhui; Tang, Weiting; Dong, Xiaofeng; Liu, Chun-feng; Xu, Tan; Cao, Yongjun; Zhong, Chongke
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Remnant cholesterol makes great contribution to residual risk of cardiovascular disease, but population-based evidence on the relationship between remnant cholesterol and atherosclerosis is rare. Common carotid artery intima-media thickness (cIMT) is an imaging marker of subclinical atherosclerosis. We aimed to explore the association between remnant cholesterol levels and cIMT in patients with ischemic stroke. Methods: One thousand four hundred ninety-six ischemic stroke patients with baseline serum lipids and carotid artery imaging data were included in this analysis. Fasting remnant cholesterol was calculated as total cholesterol minus HDL (high-density lipoprotein) cholesterol minus LDL (low-density lipoprotein) cholesterol. Abnormal cIMT was defined as mean cIMT and maximum cIMT value ≥1 mm. Logistic regression and restricted cubic spline models were used to assess the relationships between remnant cholesterol levels and abnormal cIMT. Results: The multivariable-adjusted odds ratios (95% CIs) for the highest versus lowest quartile of remnant cholesterol were 2.06 (1.46–2.91) for abnormal mean cIMT and 1.70 (1.23–2.35) for abnormal maximum cIMT. There were linear associations between remnant cholesterol levels and both abnormal mean cIMT ( P for linearity, <0.001) and abnormal maximum cIMT ( P for linearity, 0.003). Moreover, the remnant cholesterol–cIMT association remained significant in the subsample of patients with optimal LDL cholesterol levels (n=179). Conclusions: Elevated fasting remnant cholesterol levels were positively associated with mean cIMT and maximum cIMT in patients with ischemic stroke, even in patients with optimal LDL cholesterol levels. Future prospective studies are needed to verify our findings and to assess the effect of remnant cholesterol–lowering interventions in patients with ischemic stroke.